Facile esterification of carboxylic acid using amide functionalized benzimidazolium dicationic ionic liquids - Muskawar, Prashant Narayan; Thenmozhi, K.; Gajbhiye, Jayant M.; Bhagat, Pundlik Rambhau (Applied Catalysis A-General, 2014)
Herein, we report the synthesis of a new series of amide functionalized dicationic benzimidazolium based ionic liquids (DBimILs) and appraised their efficacy towards perceptive esterification of carboxylic acids with alkyl/allyl/aryl halides in presence of triethylamine. The amide groups present in this new series of DBimILs are expected to form hydrogen bonding with the carboxylic acids and this could facilitate the esterification reactions under mild conditions devoid of any added catalyst or organic solvent. The plausible mechanism for the enhanced catalytic activity in presence of this new series of ILs has been proposed. The corresponding alkyl/allyl/aryl esters isolated from this reaction were of high purity after simple extraction, which wipe out the necessity for further purification. This protocol addresses clean methodology and the efficient recyclability as well as reusability of the catalyst. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Benzimidazolium; Dicationic ionic liquids; Esterification; Homogenous catalysis

Direct synthesis of secondary amines from alcohols and ammonia catalyzed by a ruthenium pincer complex - Balaraman, Ekambaram; Srimani, Dipankar; Diskin-Posner, Yael; Milstein, David (Catalysis Letters, 2015)
Efficient and selective direct synthesis of secondary amines from primary alcohols and ammonia with liberation of water has been achieved, with high turnover numbers and with no generation of waste. In case of benzylic alcohols, imines rather than amines are obtained. This atom economical, environmentally benign reaction is homogenously catalyzed by a well-defined bipyridine based Ru(II)-PNN pincer complex.
Keywords: Alcohol; Ammonia; Homogenous catalysis; Ru-pincer complex; Secondary amine